Nutritive value of Crotalaria ochroleuca: II. The effect of supplementation on feed utilization and performance of growing sheep - Sarwatt, S.V.; Mkiwa, F.E.J.; Lwoga, A.B.; Dzowela, B.H. (International Livestock Centre for Africa, 1990)
A study carried out to determine the chemical composition of Crotalaria ochroleuca ("marejea") at three stages of growth pre-anthesis, anthesis and post-anthesis. Feeding trials were conducted to study the effect of "marejea" supplementation of low quality Chloris gayana hay on the growth rate and feed utilisation of growing sheep. Evaluates the feeding value through digestibility, growth and intake trials.